Investigation of Forced-Air Duct Leakage Phenomenon Using CFD Methods for Underground Tunnel Construction - KOSOWSKI, Maciej; ZAPLETAL, Pavel; PACH, Grzegorz (GeoScience Engineering, 2022)
Using CFD, the paper deals with a simulation of all phenomena related to forced-air duct fitted with a fan, with the emphasis on unit aerodynamic resistance and untight air ducts. We created a 3-dimentional model of the system including perforations simulating untightens in order to make a computation network. Boundary conditions were set and calculations made in ANSYS Fluent 19.1 programme. The computational results were assessed using conventional methods used in mining operations and compared with the measurement results of real air ducts in mine workings. CFD is suitable to simulate forced-air ducts and allows for their more precise design. Keywords: Auxiliary ventilation; CFD; Leaky forced-air duct; Tunnel construction.